Experimental study on the thermal management of an open-cathode air-cooled proton exchange membrane fuel cell stack with ultra-thin metal bipolar plates. (15th January 2023) - Chang, Huawei; Cai, Fengyang; Yu, Xianxian; Duan, Chen; Chan, Siew Hwa; Tu, Zhengkai
Abstract: Reliable thermal management ensures stable and efficient operation of proton exchange membrane (PEM) fuel cells. An air-cooled fuel cell stack with metal bipolar plates was developed, and 32 micro-thermocouples were arranged for in situ measurement of the temperature distribution. The resistance characteristic of the stack was tested in a wind tunnel, and then the effects of hydrogen pressure and airflow rate were analyzed. The results show that the highest and average temperatures in the stack exhibit a "parabolic" distribution as well as the maximum temperature difference of each single cell on the inlet side of the cathode. However, the temperature difference on the outlet side shows an "anti-parabolic" distribution. With a decrease in the airflow rate, the temperature uniformity in the stack deteriorates gradually. When the maximum pulse width modulation (PWM) duty cycle of the fans was 70% and the current density was 500 mA/cm 2, the temperature difference between different single cells and inside a single cell can reach 19.7 °C and 8.4 °C, respectively. The temperature uniformity in the stack at high current densities could be effectively improved by increasing the airflow rate. In addition, the hydrogen pressure and airflow rate have a certain effect on the voltage consistency. Highlights: An open-cathode air-cooled fuel cell stack with metal bipolar plates was developed. The flow resistance characteristic of the fuel cell stack was tested in a wind tunnel. In situ measurement of temperature distribution in the fuel cell stack was conducted. The effects of anode pressure and airflow rates were analyzed in detail. The temperature distributions inside a single cell and the stack were obtained respectively.